2016
DOI: 10.1364/oe.24.015757
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved luminescence imaging of intracellular oxygen levels based on long-lived phosphorescent iridium(III) complex

Abstract: Time-resolved luminescence imaging of intracellular oxygen levels has been demonstrated based on long-lived phosphorescent signal. A phosphorescent dinuclear iridium(III) complex Ir1 has been designed and synthesized, which exhibits excellent optical properties, such as high quantum yields, large Stokes shift, high photostability and long emission lifetime. The phosphorescent intensity and lifetime of complex are very sensitive to oxygen levels. Thus, the application of Ir1 for monitoring intracellular oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…PLIM imaging demonstrated that the phosphorescence lifetimes of intracellular complex 202 were 260 and 380 ns when the cells were cultured under 21% and 4% O 2 , respectively. A dinuclear Ir­(III) complex ( 203 ) localized in the cytoplasm upon internalization into living HeLa cells . PLIM imaging revealed that the phosphorescence lifetimes of the intracellular complex were 402 and 771 ns when the cells were cultured under 21% and 2.5% O 2 , respectively.…”
Section: Long-lived Luminescent Probes For Time-resolved Photolumines...mentioning
confidence: 99%
See 1 more Smart Citation
“…PLIM imaging demonstrated that the phosphorescence lifetimes of intracellular complex 202 were 260 and 380 ns when the cells were cultured under 21% and 4% O 2 , respectively. A dinuclear Ir­(III) complex ( 203 ) localized in the cytoplasm upon internalization into living HeLa cells . PLIM imaging revealed that the phosphorescence lifetimes of the intracellular complex were 402 and 771 ns when the cells were cultured under 21% and 2.5% O 2 , respectively.…”
Section: Long-lived Luminescent Probes For Time-resolved Photolumines...mentioning
confidence: 99%
“…A dinuclear Ir(III) complex (203) localized in the cytoplasm upon internalization into living HeLa cells. 595 PLIM imaging revealed that the phosphorescence lifetimes of the intracellular complex were 402 and 771 ns when the cells were cultured under 21% and 2.5% O 2 , respectively. An Ir(III)− Gadolinium(III) heterodinuclear complex 204 has been designed and synthesized for dual modal imaging.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…The schemati focused X-ra molybdenum which is simi beam with a than 100 mic Meanwhile, th s [13]; the long teractions to o gen concentrat sponsive to rad py could impr w for quantitati or proper funct m plays a signi ssue could furth of pH is critic pH level fluct me domain XL mation of these per, we presen ay beams to ex plier tube (PMT uidance in the ution lifetime i mulations. r is organized a CT imaging sy mulation setup mulation resul n section 4. , which is mounted on a motorized linear stage (MB2509Q1J-S3, Velmex, Inc., New York).…”
Section: Time Dommentioning
confidence: 99%
“…While similar to fluorescence lifetime imaging, phosphorescence lifetime imaging exhibits long luminescent lifetimes greater than fluorescent lifetimes due to their long-lived excited triplet states. Combined with time gating techniques, acquisition of these long emission lifetimes eliminates background fluorescence noise and overall improves the signalto-noise ratio (SNR) of the phosphorescent lifetime signal [13]. Lifetime information serves as probe for detection and visualization of biomolecules in tissue [14]; analysis of the lifetime signal with fractional calculus establishes correlations between the lifetime of the excited nanophosphor and the biomolecule.…”
Section: Introductionmentioning
confidence: 99%
“…Iridium complexes have also been actively targeting for their use in biological imaging and diagnostics, [13][14][15][16][17] and imaging probes for specific organelles, including mitochondria have been devloped. [18][19][20][21][22][23][24][25][26] Biscyclometalated iridium(III) complexes bearing dppz-like ligands have also been investigated.…”
mentioning
confidence: 99%